Pengaruh Pemberian Tracer Terhadap Ketepatan Penyimpanan Berkas Rekam Medis Di RSU Purbowangi - Citra Wiguna Bakti Bakhtiar; Santi Lathifatur Rohmah; Galih Cahya Panuntun (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
Medical record is an inpatient outpatient treatment that stores important data and very important benefits, one of which is as a basis and guidance in planning and analyzing actions and services that will be provided to patients after checking and treatment. Based on the observations that have been made, it turns out that there are several medical record files that are missing and their placements are swapped from other medical record files, this is because too many medical records are accommodated and the lack of medical recording methods in an effort to minimize the occurrence of inaccuracies in storing medical record files. Efforts to solve the problem are to provide a tracer to the medical record file that has just been taken so that when returning the medical recorder it is not confused in finding and placing the correct medical record file. After applying the tracer system, it turns out that there is an effect of giving a tracer on the accuracy of the medical record file.